Menumbuhkan Cinta Tanah Air Melalui Teknologi Dalam Konteks Wawasan Kebangsaan Pada Generasi Muda - Ester Rosa Komara; Muhammad Gilang Putra Tryana; Neila Zira Alfiyah; Ratu Azmi Muthmainna Shauban; Maulia Depriya Kembara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The increasing use of social media in society, especially among teenagers, shows significant technological advances. The easier access to the Internet and social networks, the negative impacts of globalization especially afflict many young people who exhibit violent, pragmatic, desperate, selfish, and hopeless behavior. The cyberspace industry creates a young generation that is passive, does not think critically, is negatively reconciled, and is not creative. Positive campaigns on social media and active participation of the younger generation in sharing positive experiences and stories about their homeland can be a catalyst for building a positive atmosphere in the digital realm. In writing this article, the author used two methods, namely, interviews and literature studies. In the interview method, the author interviewed several sources to find out their knowledge and opinions about the national vision. Then by using the literature study method, the author sources his data through books, and other scientific articles related to the national vision.